Neural field theory of adaptive effects on auditory evoked responses and mismatch negativity in multifrequency stimulus sequences - Babaie-Janvier, Tahereh; Gabay, Natasha C.; McInnes, Alexander; Robinson, Peter A. (Frontiers in Human Neuroscience, 2024)
Physiologically based neural field theory (NFT) of the corticothalamic system, including adaptation, is used to calculate the responses evoked by trains of auditory stimuli that differ in frequency. In oddball paradigms, fully distinguishable frequencies lead to different standard (common stimulus) and deviant (rare stimulus) responses; the signal obtained by subtracting the standard response from the deviant is termed the mismatch negativity (MMN). In this analysis, deviant responses are found to correspond to unadapted cortex, whereas the part of auditory cortex that processes the standard stimuli adapts over several stimulus presentations until the final standard response form is achieved. No higher-order memory processes are invoked. In multifrequency experiments, the deviant response approaches the standard one as the deviant frequency approaches that of the the standard and analytic criteria for this effect are obtained. It is shown that these criteria can also be used to understand adaptation in random tone sequences.A method of probing MMNs and adaptation in random tone sequences is suggested that make more use of such data.